2016
DOI: 10.3390/rs8060458
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spatial Sampling Interval on Roughness Parameters and Microwave Backscatter over Agricultural Soil Surfaces

Abstract: Abstract:The spatial sampling interval, as related to the ability to digitize a soil profile with a certain number of features per unit length, depends on the profiling technique itself. From a variety of profiling techniques, roughness parameters are estimated at different sampling intervals. Since soil profiles have continuous spectral components, it is clear that roughness parameters are influenced by the sampling interval of the measurement device employed. In this work, we contributed to answer which samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
2
11
0
3
Order By: Relevance
“…Regarding the influence of small-scale components, the results demonstrate that eliminating these small-scale roughness components from the profiles caused a strong variation in the values of horizontal parameters, while vertical ones were more insensitive. This is in agreement with Barber et al [30] who observed that when the sampling interval increased, s decreased slightly and l increased causing the separability between different roughness classes to decrease. The results also confirm that l values did not stabilize with long profiles, but showed rather an increase in their variability [19], [26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding the influence of small-scale components, the results demonstrate that eliminating these small-scale roughness components from the profiles caused a strong variation in the values of horizontal parameters, while vertical ones were more insensitive. This is in agreement with Barber et al [30] who observed that when the sampling interval increased, s decreased slightly and l increased causing the separability between different roughness classes to decrease. The results also confirm that l values did not stabilize with long profiles, but showed rather an increase in their variability [19], [26].…”
Section: Discussionsupporting
confidence: 93%
“…Barber et al [30] evaluated the influence of sampling interval on the SSR statistics over agricultural soils and observed that class differences were reduced as the measurement interval increased. They also recommended intervals of 15 and 5 mm for L-and C-bands, respectively.…”
mentioning
confidence: 99%
“…The dense point cloud was then rotated to the true X, Y, and Z directions using markers that were manually placed on images showing the measuring tapes and assuming Z = 0 for all points (i.e., models then display the surface elevation relative to the plain defined by the two measuring tapes). In the third step, the DEM and the ortho-mosaic were processed with a pixel spacing of 0.2 cm, of 0.1 cm respectively, meeting the sampling interval for C-Band data (0.5 cm) recommended by [44]. Table 2 reports the accuracies of the processed ground-based DEMs in X, Y, and Z direction.…”
Section: Fieldwork and Samplingmentioning
confidence: 99%
“…Usualmente, el método SPM también es usado el límite de su rango de validez, s ∼ 0,05λ , produciendo resultados satisfactorios [9,10,13,14]. En el caso de suelo desnudo y para el rango de microondas en banda L (λ = 25 cm), la condición de validez se cumple si la altura rms de la superficie cumple s < 1,25 cm, lo que es una hipótesis razonable para suelos de agricultura sin vegetación, en donde s ∼ 1 cm [5,6,15].…”
Section: Cálculo Del Patrón De Interferenciaunclassified
“…En el marco de este esquema, cuando un satélite de la red GPS ilumina una superficie, se genera una señal dispersada que depende, principalmente, de dos aspectos: i) la geometría de la superficie; ii) las características dieléctricas de la misma. Teniendo en cuenta que siempre se trabaja con superficies reales, los perfiles de las mismas no se describen a través de funciones analíticas sino mediante parámetros estadísticos [5]. Cuando se monitorea superficies sin vegetación (suelos desnudos) las características geométricas se definen a través de la altura rms de la superficie (s) y de la función de autocorrelación entre dos puntos de la misma (ρ(x, x )); comúnmente, esta función es una Gaussiana con media cero y una longitud típica, que es la longitud de correlación (l).…”
Section: Introductionunclassified